Theories about technology accepentace: why the users accept or reject the information technology? - Silva, Patrícia Maria (2008)
The acceptance and use of information technology is a subject that has received the attention of researchers and professionals in the Computer Science, Information Systems and Information Science, because the prospect that a well-developed system will be used, since start with the assumption that good solutions in software, can bring competitive advantage to businesses and individuals. Understanding why people use or discard computers has become one of the most challenging issues in research on information systems. In literature, it is possible to identify various theories that attempt to predict the impact of technology on human behavior however this article will make a brief review of literature on three theories. They are: Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB) and finally Technology Accepentace Model (TAM), model which will better explained, because it is the best known and used in the area of information systems.